Thoracoscopic sleeve segmentectomy for bipulmonal non-small-cell lung cancer with curative approach. (15th October 2020) - Herrmann, Dominik; Gencheva-Bozhkova, Plamena; Oggiano, Melanie; Hecker, Erich
Abstract: A patient with simultaneous bilateral non-small-cell lung cancer underwent a thoracoscopic sleeve segmentectomy on the right side to avoid lobectomy in curative approach. The patient also had a second, left-sided tumour requiring at least a left-sided sleeve upper lobectomy for complete resection. In anticipation of the second pulmonary resection in a patient whose lung function was already impaired by the first operation, we opted for a thoracoscopic approach with fast recovery. The left-sided operation was performed 60 days after the right-sided sleeve segmentectomy without any complications. Abstract : We present the case of a 66-year-old patient with simultaneous non-small-cell lung cancer (NSCLC).